Fabrication of flower-stacked structured microparticles encapsulated with stem cells and growth factor to the potential treatment of intervertebral disc degeneration. (August 2022) - Dong, Zhen; Chen, Shutao; Wang, Lintao; Qi, Peng; Wei, Liyan
Abstract: Intervertebral disc degeneration is one of the most complicated and leading causes of low back pain which is caused by aging, work pressure, genetic and environmental factors. Generally, treatment of intervertebral disc degeneration complications exists more challenges and meanwhile researchers are trying finding solutions through stem cell biology, materials technology, nanomedicine therapies. Mainly, fabrication of active polymeric biomaterials has very similar biological and physiological properties of natural extracellular matrix and possess promising therapeutic potential in the tissue regenerative medicine. The combined therapies based on transplanted stem cells and growth factors are also highly suggested to obtain positive therapeutic outcomes for intervertebral disc degeneration regenerations. To achieve successful implantations for intervertebral disc degeneration, blended polymeric porous microspheres with flower-stacked structure is developed to allow sustained released of connective tissue growth factor signaling molecules and also carried of bone marrow-derived mesenchymal stem cells. The flower-stacked polymeric microspheres were prepared by simple heating-cooling method and characterized by spectroscopic and microscopic techniques. The morphological analysis confirmed that the efficacious formation of unique spherical morphology with porous nature to allow volume restoration property. The connective tissue growth factor immobilized polymeric microspheres was incessantly released the signaling molecules for 18 days in vitro and also have outstanding in vitro cell compatibility and adhesive ability, due to the unique morphology of the polymeric microspheres. As observed by in vitro and in vivo analyses, connective tissue growth factor immobilized polymeric microspheres can provide effective in vitro chondrogenic differentiations of stem cells and strongly influences to intervertebral disc degeneration model. Graphical Abstract: ga1 Highlights: Designed and Developed leaf-like structured microspheres by blended components. Improve sustained released of connective tissue growth factor from microspheres. Transplantation of stem cells to achieve Intervertebral disc degeneration treatment. Disc regeneration could be achieved by effective chondrogenic differentiations.